Perbandingan Proses Clearing Antara Xylol dan Minyak Gandapura Terhadap Kualitas Preparat Awetan Kutu Tikus ( Xenopsylla Cheopis ) - Anggi Nur Wijayanti; Erni Yohani Mahtuti; Muhammad Basyarudin (Lembaga Pengembangan Kinerja Dosen, 2024)
Xylol is a dangerous and toxic substance. The use of Xylol in the Anatomical Pathology laboratory is considered common for the stage of “cleansing” both for the process of tissue entry and sanation. Xylol is used in Anatomical Pathology laboratories because it is soluble with dehydrating agents and can disintegrate paraffin as a drying agent. Xylol is part of Gandapura oil hydrocarbons. Research aimed at finding alternative substitutes for xilol was conducted using Gandapura oil using experimental methods. Samples using Mouse Pins (Xenopsylla cheopis) can show thinning of the skin layer with connective tissue due to the use of “cleansing” agents.with Xylol 15 and 30 minutes Coconut oil 15 and 30 minutes. The parameters used are a description of the color quality of the preparation, the clarity of the preparation and the thoroughness of the preparation. The results of the study showed A1 preparations with a result of 3 bright,3 moderately bright, 2 clear, 4 MImoderately clear and 6 hours. A2 preparation with results of 2 bright, 4 moderately bright 3 clear, 3 moderately clear, and 6 minutes. Preparation B1 with a result of 4 bright 2 well-lit, 5 rows 1 fairly clear and 6 hours. B2 preparation with a result of 1 bright, 5 moderately bright, 2 clear 4 fairly clear 5 grains and 1 out of order. The use of coconut oil decrypted gives a good quality to the preparation compared to using Xylol, but it cannot be used for a long time.